UTILIZATION OF LOCAL MICROORGANISMS (MOL) WHITE COOPERATE VEGETABLE (Brassica Rapa) AS AN ACTIVATOR IN THE PROCESS OF COMPOSTING ORGANIC VEGETABLE WASTE - Nur Afni Maftukhah (Jurnal Inspirasi Kesehatan, 2024)
Background: One of the big problems being experienced by big cities in Indonesia and cities in other countries is waste. For For people living in villages, the waste problem can still be managed and It is used for various needs, one of which is fertilizer in an effort to fertilize agricultural land through the composting process with using Local Microorganisms (MOL). White mustard greens are wrong one material that can be used as raw material for making MOL. Research Objective: The purpose of this research is to find out white mustard greens as activator in the composting process of organic vegetable waste. Research Method: Which used in this research was making MOL white mustard greens as a composting activator. Composting using a basket semi aerobic by measuring the percentage of waste reduction, pH and temperature. Results: shows that giving 100% MOL shows the highest reduction in organic waste was 64% when compared with other treatments and controls. pH and temperature of the final compost in the treatment the highest were 6.9 and 27.9 0C respectively. In addition, the addition of MOL 100% also has the second highest effectiveness in reducing organic waste after giving MOL 80%, namely 59%. Giving MOL during the process Composting has a role in accelerating the waste reduction process organic compared to without the addition of MOL. Conclusion: research result Descriptive average pH value of 6.80-7.5 from the use of white mustard greens (Brassica rapa) as an activator in composting organic vegetable waste.